Worsening functional status in nephrogeriatrics needs to be accounted for when clinically assessing CKD advancement in addition to GFR; supporting evidence based on the practical application of theoretical modelling - Magdalena Wisniewska; Stanislaw Niemczyk (BMC Geriatrics, 2022)
Abstract The incidence of chronic kidney disease (CKD) has been found to increase with age. This has resulted in an increase in the number of elderly patients undergoing renal replacement therapy. There is a significant risk of error in making treatment decisions in patients with advanced CKD based solely on biochemical parameters of renal function, if the changes in the functional status of patients' health are not taken into account. Aim To determine the interrelated dependencies between chronic kidney disease with the functional status of patients aged over 65 years and to elucidate differences in functional status between CKD patients and controls. Methods Patient subjects were qualified according to their assessed outcomes from the study protocol, which were achieved by: geriatric interview, assessing functional status by the IADL, Barthel and Tinetti tests together with assessing kidney function by performing laboratory tests of glomerular filtration rate (GFR), creatinine and urea. Subjects were divided into two groups: method 1—according to GFR and method 2—according to GFR and functional test results. The data were statistically analysed by structural equation modelling and k-means. Results Positive relationships were found between the CKD stage and comorbidity (β = 0.55, p < 0.01), along with the number of medications taken and age (respectively β = 0.19, p = 0.001 and β = 0.30, p < 0.001). A highly negative relationship was observed between the CKD stage and the Tinetti test results (β = -0.71, p < 0.001), whilst more moderate ones were found with the IADL and Barthel scores (respectively β = -0.49, p < 0.001 and β = -0.40, p < 0.001). The patient groups demonstrated differences in health status when selected by method-2 for: age, comorbidity, number of medications taken, fitness test outcomes (Tinetti, Barthel and IADL tests at p < 0.005). Those groups divided according to GFR, however only showed differences in age, comorbidity and the number of medication taken (p < 0.005). Conclusions The functional status worsens in geriatric patients suffering from CKD. It may thus be important to also account for disruptions to functional status when assessing CKD advancement in the elderly in addition to the GFR. The biggest problems for the over 80 s suffering from CKD are gait and balance disorders, leading to a high risk of falls. Another common problem is polypharmacy, found in both the geriatric population and particularly in those suffering from CKD.